Perception and practice of gender among Nepalese in Portugal: A male perspective - Dahal, Sanjeev (2016)
The study looked into the perception and practice of gender among Nepalese men in Portugal. It explored gender related discourses and practices through these key research questions: i) how do Nepalese men migrants in Portugal perceive gender relations; ii) how are Nepalese men migrants in Portugal performing gender and iii) has migration affected the perception and practice of gender in Nepalese men. The study engaged in micro-ethnographic method using qualitative interviews and participant observation as tools. Five Nepalese men were interviewed during ethnographic field work which was substantiated with participant observation in private and public sphere of the life of Nepalese in Lisbon and Faro districts in Portugal. It was mentioned in the discourses of Nepalese men that migration and the resultant new social context of Portugal had a significant impact on how they perceive and practice gender which facilitated their understanding of unequal gender relations in Nepal as well as their move towards egalitarian gender relations. The study concludes that Nepalese men experienced significant changes in their perception of gender relation with women; but these changes were yet to be adequately reflected in their practices.